2016
DOI: 10.1021/acs.macromol.5b01827
|View full text |Cite
|
Sign up to set email alerts
|

Toward an Effective Control of DNA’s Submolecular Conformation on a Surface

Abstract: DNA adopts different conformations based on its environment. We reveal conditions that either preserve the DNA’s physiological B-conformation, even upon its placement in UHV, or lead to a partial B-form to A-form reorganization upon DNA’s deposition on a surface. We use high-resolution AFM to image DNA with a well-defined number of base pairs deposited on mica. To enable the DNA’s adhesion, we either add divalent cations to the DNA solution or functionalize the surface with a silane layer. The contour length o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
99
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 48 publications
(102 citation statements)
references
References 53 publications
3
99
0
Order By: Relevance
“…However, all these exceeded the lengths measured for the pBR322 control. We verified these differences by imaging the nucleoprotein complexes on the APTES-modified mica surface, which was due to strong charge interactions kinetically trapping the complexes and, thus, better preserving their three-dimensional configuration (3841). When deposited on the APTES-treated surface, the morphology of the nicked DNA changed significantly.…”
Section: Resultsmentioning
confidence: 81%
“…However, all these exceeded the lengths measured for the pBR322 control. We verified these differences by imaging the nucleoprotein complexes on the APTES-modified mica surface, which was due to strong charge interactions kinetically trapping the complexes and, thus, better preserving their three-dimensional configuration (3841). When deposited on the APTES-treated surface, the morphology of the nicked DNA changed significantly.…”
Section: Resultsmentioning
confidence: 81%
“…TERS exploits the near‐field enhancement generated by excitation of surface plasmons at the laser‐irradiated apex of a metal or metallized SPM tip . A few research groups have applied TERS to study nucleic acids . The technique was applied to read and identify DNA bases and was proposed as a potential method to determine DNA base sequences .…”
Section: Band Assignments For Ter and Confocal Raman Spectra Of 500 Bmentioning
confidence: 99%
“…The molecular structure of individual double strand breaks (DSBs) was characterized using TERS by Lipiec et al Based on spectral data, it was found that DSBs result from cleavage at the 3′ and 5′ bonds of the deoxyribose unit upon exposure to UV C radiation . TERS was also used in DNA conformation studies . The most common form of the DNA, which is present in physiological salt concentrations (neutral pH), is B‐conformation.…”
Section: Band Assignments For Ter and Confocal Raman Spectra Of 500 Bmentioning
confidence: 99%
See 1 more Smart Citation
“…But the molecules in 2D remain stiffer, even for lengths shorter than 3400 bp [2-5, 7, 8]. Moreover, transition from B-DNA to A-DNA during the imaging in the dry air can also cause DNA stiffer [33][34][35][36]. To avoid this structural transition, DNA molecules in fig 1 were scanned in solution and biological conditions.…”
Section: Figmentioning
confidence: 99%